Phenotypic and molecular detection of metallo-β-lactamase-producing Pseudomonas aeruginosa isolates from patients with burns in Tehran, Iran - Azimi,Akram (2018)
Abstract INTRODUCTION: Health care-associated infections caused by metallo-β-lactamase (MBL)-producing Pseudomonas aeruginosa are a significant growing concern in patients with burns worldwide. The aims of this study were to determine the antibiotic susceptibility of and detect the presence of MBLs among P. aeruginosa isolates and assess their clonal relationship using enterobacterial repetitive intergenic consensus (ERIC)-PCR. METHODS: Non-duplicated clinical isolates (160) of P. aeruginosa were collected from patients with burns at the Motahari Hospital in Tehran, Iran. All isolates were identified using standard laboratory methods and further characterized for antimicrobial susceptibility. Any carbapenem-resistant isolates were then examined for MBL production by the E-test and MBL-encoding genes were detected by PCR. The clonal relatedness of MBL-producing isolates was assessed by ERIC-PCR. RESULTS: For multidrug-resistant isolates, the highest rates of susceptibility were observed for colistin 160 (100%), polymyxin B 160 (100%), and ceftazidime 32 (20%). In total, 69 (43.7%) isolates were identified as MBL producers. Twenty-eight (17.5%) isolates were positive for the bla VIM-1 gene followed by the bla IMP-1 (15.6%) and bla SPM-1 (5.6%) genes. ERIC-PCR revealed three separate genotypes, where type A (76.8%) was the most prevalent, followed by B (20.3%), and then C (2.9%). CONCLUSIONS: Our present study found that the bla IMP-1 and bla VIM-1 genes were present at a significant frequency and also detected the bla SPM-1 gene in P. aeruginosa isolates for the first time, highlighting the need for establishing suitable infection control measures to successfully treat patients and prevent further spread of these resistant organisms among patients with burns.